Mooring the global archive : a Japanese ship and its migrant histories - Dusinberre, Martin, 1976- (Cambridge oceanic histories., 2023)
Martin Dusinberre follows the Yamashiro-maru steamship across Asian and Pacific waters in an innovative history of Japan's engagement with the outside world in the late-nineteenth century. His compelling in-depth analysis reconstructs the lives of some of the thousands of male and female migrants who left Japan for work in Hawai'i, Southeast Asia and Australia. These stories bring together transpacific historiographies of settler colonialism, labour history and resource extraction in new ways. Drawing on an unconventional and deeply material archive, from gravestones to government files, paintings to song, and from digitized records to the very earth itself, Dusinberre addresses key questions of method and authorial positionality in the writing of global history. This engaging investigation into archival practice asks, what is the global archive, where is it cited, and who are 'we' as we cite it? This title is also available as Open Access.